Pancasila Revitalization for the Enforcement of Non-Discriminatory Principle of Global Business Competition to Small Entrepreneurs - Tentero, Reggie (KnE Social Sciences, 2023)
Pancasila, in the 5th precept, is social justice for all Indonesians. This means that justice that is the ideal of the Indonesian nation is justice that is socially just. The revitalization of Pancasila is the key to restoring and growing social justice in business competition in the global era for small business actors. The implementation of Pancasila revitalization of small business actors in global business competition can be done by making waivers to the Ministerial Conference to follow up on the non-discriminatory principle of business competition against small business actors to get exemptions, so that the value of social justice contained in Pancasila can be realized, especially for small business actors. The existence of the non-discriminatory principle on the implementation of Pancasila revitalization of global business competition to small entrepreneurs is still recognized for its existence, considering that there is no follow-up to the disharmony of regulations in the WTO and business competition law in Indonesia, especially regarding the application of non-discriminatory principles to business competition specifically for small business actors. The method used in this study is normative juridical with a problem approach that has the purpose and purpose of reviewing applicable laws and regulations as well as literature with a theoretical concept, then connected with the problems that are the subject of discussion discussed in this research writing. Keywords: Pancasila, non-discriminatory principles, global business competition, small/medium enterprises